Water supply services in Greater Tzaneen Municipality : A case study of Lenyenye Township - Letsoalo, Masilo Simon (University of Limpopo (Turfloop Campus), 2012)
The aim of the envisaged study is to investigate the water supply services in Lenyenye Township, in Greater Tzaneen Municipality and to derive suggestions and recommendations for improvement based on the objectives decomposed into the following: To review the extent and the magnitude of Water Supply problems and to identify, analyze the underlying causes of the water supply problems because the basic infrastructure provision of water supply is very poor and dismal across the area. Water serves as a basic need to which everybody has the right to access, be it for consumption or irrigation this service is, unfortunately, disrupted by many factors. The findings in the study for poor water supply emanate from many common causal factors such as management skills, technical challenges and illegal connections. Only two methods were employed to collect data in the study. Data collection was done by using the questionnaire and the interview methods and the interview involved direct personal contact with the participants who answered questions. A survey questionnaire was used to obtain data pertaining to water supply services from the representatives of water supply institutions. Recommendations in the study are based on the findings such as prioritization of effective water supply for Lenyenye township, community consultation and participation, addressing capacity constrains in the Municipality such as human resources, water service infrastructure, and skills development.
Thesis (M.Dev.) --University of Limpopo, 2012
Keywords: Water supply services; 363.610968; Municipal water supply -- South Africa; Local government -- South Africa -- Limpopo